Expression levels of miRNA-127 in a cohort of HIV-positive and HIV-negative Diffuse Large B-Cell Lymphoma. - Olivier, Chera (Department of Clinical Laboratory Science, 2019)
Diffuse Large B Cell Lymphoma is one of the most common Non-Hodgkin’s Lymphomas. It is prevalent in older age patients but as of late there has been a rise in the younger population in South Africa due to the rise of HIV. DLBCL is quite an aggressive cancer but can be treated, however the relapse rate is high. There are prognostic indicators which can be seen as factors which can be indicative of a poor outcome for patients. Micro-RNA(miRNA) are small non-coding RNA which can remain stable to be tested. There are several miRNAs which may be linked to prognosis, including miRNA-21 whose upregulated expression has been associated with bad prognosis. However, this is not specific to DLBCL and some studies done have indicated that there may be other miRNAs which are better suited to be biomarkers for DLBCL. Studies have pointed to the direction of miRNA127 as a more reliable microRNA in its association with prognosis in breast, cervical and gastric cancer as well as DLBCL. Objective: The primary aim of this study was to determine the association between miRNA127 and prognostic markers including immunohistochemical stains, survival status and the IPI factor to determine its significance as a prognostic indicator. An additional aim was to determine the correlation between HIV status and expression level of miRNA-127. Design: A total of 42 DLBCL cases were collected from the archive of Division of Anatomical Pathology, University of Cape Town/NHLS Groote Schuur. The H&E slides were assessed before RNA was extracted from FFPE tissue and converted to cDNA. Real time quantitative RT-qPCR was used to assess the expression of the microRNA. Normal tissue as well as reactive lymph node tissue were used as controls. The expression patterns were also correlated to the clinical information to determine if there was any relationship. Results: Out of the 42 cases used, 10 cases were silenced, and 31 cases had high miRNA-127 expression. The expression levels were correlated with the IPI factors and the other clinicopathologic features however no significant conclusion were determined. Conclusion: We found high expression of miRNA-127 cases in the majority of the DLBCL cases. There was no correlation between HIV status and the expression of miRNA-127, nor between the expression and any of the clinicopathological feature. For future studies it is advised that more equally distribution of samples (both HIV status and gender) are obtained, this will allow for a better comparative study.